Peter the Venerable and Islam - Kritzeck, James Aloysius (Princeton Studies on the Near East, 2016)
For over four centuries the principal source of Christian European knowledge of Islam stemmed from a project sponsored by Peter the Venerable, ninth abbot of Cluny, in 1142. This consisted of Latin translations of five Arabic works, including the first translation of the Koran in a western language. Known as the Toledan Collection, it was eventually printed in 1543 with an introduction by Martin Luther. The abbot also completed a handbook of Islam beliefs and a major analytical and polemical work, Liber contra sectam Saracenorum; annotated editions of these texts are included in this book. Originally published in 1964. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.